ANALISIS TENTANG PERSEPSI GURU TERHADAP PRINSIP BELAJAR KEAKTIFAN SISWA KELAS VII SMP NEGERI 37 PEKANBARU - Harfia, Firda Mariam; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by problems that arise in the principle of learning student activeness as seen from individual assignments and group assignments. The formulation of the problem in this study is how the teacher's perception of the principle of active learning of grade VII students at SMP Negeri 37 Pekanbaru. The research objective was to determine how the implementation of the principles of learning activeness of Class VII students at SMP Negeri 37 Pekanbaru. The benefits of research results for teachers are to provide an overview of teachers 'perceptions of the principles of learning activeness of class VII students at SMP Negeri 37 Pekanbaru and become a reference for how active grade VII students are according to teachers' perceptions of the learning principles of seventh grade students at SMP Negeri 37 Pekanbaru. This research method is a descriptive quantitative method of data collection instruments used in this study, namely a questionnaire consisting of 25 questions with 2 indicators. The population in this study were class VII teachers of SMP Negeri 37 Pekanbaru. The sample in this study was taken using a saturated sample technique. Based on the results of the research conducted, it can be concluded that the overall data regarding teachers' perceptions of the principles of learning activeness of class VII students at SMP Negeri 37 Pekanbaru are in the